2017
DOI: 10.1002/gps.4784
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial behaviour management programme for home‐dwelling people with dementia: A cluster‐randomized controlled trial

Abstract: The implementation of the BASE programme resulted in a reduction of challenging behaviour of home-dwelling people with dementia. Future research should examine the long-term effects of behaviour management programmes on behaviour, nursing home placement, and hospital admission of home-dwelling people with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 45 publications
0
46
0
Order By: Relevance
“…One aspect regarded as crucial to warranty the effectiveness of psychosocial interventions is the provision of tailored activities, particularly for home-dwelling PwD ( 9 , 46 ). As the caregiver group usually varies from adolescents (including “adult children”), adults, spouses to professional care providers, individualized dyadic interventions shall be designed in any dyadic compositions to reduce the caregiver social strain ( 47 ) and improve PwD functional ability ( 47 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One aspect regarded as crucial to warranty the effectiveness of psychosocial interventions is the provision of tailored activities, particularly for home-dwelling PwD ( 9 , 46 ). As the caregiver group usually varies from adolescents (including “adult children”), adults, spouses to professional care providers, individualized dyadic interventions shall be designed in any dyadic compositions to reduce the caregiver social strain ( 47 ) and improve PwD functional ability ( 47 ).…”
Section: Resultsmentioning
confidence: 99%
“…A number of them have been delivered to support caregivers ( 60 ). The types of intervention vary widely, as does the quality of the methods used ( 46 ). Person-centered care approaches designed to home settings have been performed using observational tools and practice development cycles, such as the Dementia Care Mapping™ (DCM™) ( 61 ).…”
Section: Resultsmentioning
confidence: 99%
“…This line of research emphasizes the need for programs or interventions (e.g., formal assistance programs) to be developed to support caregiving responsibilities and ultimately reduce burden and improve outcomes among patients and caregivers alike. For example, there is a cluster-randomized study that assessed psychosocial behavior management programme for home-dwelling people living with dementia [ 58 ]. This programme reduced challenging behaviors, which were evaluated by the Neuropsychiatric Inventory.…”
Section: Discussionmentioning
confidence: 99%
“…The Japanese adaptation of the BPSD-registry, called DEMBASE ® , has been developed with a focus on care managers of in-home service users with dementia. The results of a cluster-randomized controlled trial indicated a reduction in neuropsychiatric symptoms upon application of the adapted program [25], with a medium observed effect size (Cohen's d ppc = 0.52). Based on the results, the program was implemented for routine dementia care in the Tokyo metropolitan area in April 2018.…”
Section: Introductionmentioning
confidence: 98%
“…The BPSD-registry is based on an interdisciplinary team approach, and was primarily established for use in nursing homes. Adapted forms of the program have been developed in Denmark [23], the Netherlands [24], and Japan [25].…”
Section: Introductionmentioning
confidence: 99%